1. a) |x - 1| + 2|x - 3| = 5 - x Если x < 1, то |x - 1| = 1 - x, |x - 3| = 3 - x 1 - x + 2(3 - x) = 5 - x 1 - x + 6 - 2x = 5 - x 1 + 6 - 5 = x + 2x - x 2x = 2; x = 1 - не подходит, потому что x < 1 Если x ∈ [1; 3), то |x - 1| = x - 1; |x - 3| = 3 - x x - 1 + 2(3 - x) = 5 - x x - 1 + 6 - 2x = 5 - x 5 - x = 5 - x Это верно при любом x ∈ [1; 3) Если x >= 3, то |x - 1| = x - 1; |x - 3| = x - 3 x - 1 + 2(x - 3) = 5 - x x - 1 + 2x - 6 = 5 - x 3x + x = 5 + 6 + 1 4x = 12 x = 3 ответ: x ∈ [1; 3]
Я уже решал эту задачу 1) |x - 1| + 2|x - 3| = 5 - x Если x < 1, то |x - 1| = 1 - x, |x - 3| = 3 - x 1 - x + 2(3 - x) = 5 - x 1 - x + 6 - 2x = 5 - x 1 + 6 - 5 = x + 2x - x 2x = 2; x = 1 - не подходит, потому что x < 1 Если x ∈ [1; 3), то |x - 1| = x - 1; |x - 3| = 3 - x x - 1 + 2(3 - x) = 5 - x x - 1 + 6 - 2x = 5 - x 5 - x = 5 - x Это верно при любом x ∈ [1; 3) Если x >= 3, то |x - 1| = x - 1; |x - 3| = x - 3 x - 1 + 2(x - 3) = 5 - x x - 1 + 2x - 6 = 5 - x 3x + x = 5 + 6 + 1 4x = 12 x = 3 ответ: x ∈ [1; 3]
2)a²-9b = ?
a²-9=(a+3)(a-3)
a²-9b²=(a+3b)(a-3b)
3)a²-4a+4=(a-2)(a-2) = (a-2)²
4)3a+3-na-n=3(a+1)-n(a+1)=(a+1)(3-n)
8x(1+2x)-(4x+3)(4x-3)=2x
8x+16x² - (16x²-9)=2x
8x+16x²-16x²+9=2x
8x+9=2x
6x=-9,x=-9/6, x=-3/2, x=-1,5